Enhancement of combustion and radiation performances in a counterflow double‐channel combustor with pin fins for micro‐thermophotovoltaic system. (14th September 2021) - Gao, Wei; Yan, Yunfei; Zhang, Weiwei; Shen, Kaiming; He, Ziqiang; Zhang, Chenghua
Summary: As one vital role component of micro‐thermophotovoltaic (MTPV) system, the combustion characteristics of the micro‐combustor directly affect the wall temperature distribution and the MTPV system efficiency. Combined with the advantages of counterflow and pin rib arrangement, a counterflow double‐channel micro‐combustor with pin fins (combustor C) was built to enhance the heat transfer and improve the wall temperature. The combustion performances and radiation performances of single‐channel micro‐combustor (combustor A), counterflow double‐channel micro‐combustor (combustor B), and combustor C were investigated and compared under different mass flow rates (4~12 × 10 −5  kg/s) and equivalence ratios (0.6~1.4). Results show that the pin fin is of positive significance for the fixation of flame root to improve the combustion stability, combustion efficiency, and radiation energy when the total mass flow rate is high, especially. When the mass flow rate is low, the combustion efficiency of combustor C is the lowest due to the limitation of combustion space. However, with the increase of the mass flow rate, the combustion characteristics of combustor C are the best due to the flame front area is larger among the three combustors and the flame root position is closer to the inlet area. The radiation energy, radiation efficiency, and mean temperature of the upper wall of the combustor C are significantly higher than other combustors under the same conditions. When the total mass flow rate is 12 × 10 −5  kg/s, the radiation energy of combustor C is 0.51 times and 0.36 times that of combustor A and B, respectively. When the equivalence ratio is 1.0, the mean upper wall temperature of combustor C is 175.87 and 128.904 K higher than of combustor A and B, respectively. The counterflow double‐channels combustors have better wall temperature uniformity than single‐channel combustor under a wide range of working conditions.